MANAJEMEN PENDIDIKAN DAN PELATIHAN KEAHLIAN GANDA GURU SEKOLAH MENENGAH KEJURUAN - Ukhti Rochmawati; Agus Timan; Desi Eri Kusumaningrum (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2019)
Abstract: Research objectives to describe the management of education and training undertaken by the training institutions for the implementation of the program. Research using qualitative approach. The data collected by interview, observation, and documentation methods. Results of research: (1) program planning of multiple expertise PPPPPTK BOE Malang was start from an analysis of the needs of teachers, drafting the budget, recruitment of participants, to making proposals of activities; (2) organizing was done by the Division of proposals to work units, and continued by coordonation meeting for committee involement; (3) training implementation by using  in-on-in model was done with provisioned speaker and attendees, and the strategies of andragogy approach. The implementation of the learning was begin with the opening to learning in each classroom; (4) evaluation of the implementation of the multiple expertise program at PPPTK BOE Malang was consist of participant’s assesment, speaker of theacer’s assesment, and organizer’s assesment.. Keyword: Educational and Training Management, Multiple Expertise Abstrak: Tujuan penelitian untuk mendeskripsikan manajemen pendidikan dan pelatihan yang dijalankan oleh lembaga pelatihan untuk pelaksanaan program keahlian ganda. Penelitian menggunakan pendekatan kualitatif. Data dikumpulkan dengan metode wawancara, observasi, dan dokumentasi. Hasil penelitian: (1) Perencanaan program keahlian ganda di PPPPPTK BOE Malang  mulai dari analisis kebutuhan guru, penyusunan anggaran, perekrutan peserta pelatihan, sampai dengan pembuatan proposal kegiatan; (2) pengorganisasian dilakukan dengan pembagian proposal kepada unit kerja, dilanjutkan rapat koordinasi dan pelibatan ke dalam kepanitiaan; (3) model pelaksanaan pelatihan in-on-in dengan dilakukan pembekalan terhadap narasumber dan peserta dengan strategi pembelajaran pendekatan andragogi, kemudian pada pelaksanaan pelatihan diawali dengan pembukaan hingga pembelajaran di kelas masing-masing; (4) evaluasi pelaksanaan program keahlian ganda di PPPPTK BOE Malang menyangkut penilaian peserta, penilaian narasumber atau pengajar, dan penilaian penyelenggara. Kata Kunci: Manajemen Pendidikan dan Pelatihan, Keahlian Ganda